7x + 2(2x - 5) - (-5x + 3) can be simplified as follows:
7x + 4x - 10 + 5x - 3
= 16x - 13
Therefore, 7x + 2(2x - 5) - (-5x + 3) is equivalent to 16x - 13.
7x+2(2x-5)-(-5x+3) equivalents.
7 answers
is this equivalent 6x - 13
Let's simplify the expression again and check if it is equivalent to 6x - 13:
7x + 2(2x - 5) - (-5x + 3)
= 7x + 4x - 10 + 5x - 3
= 16x - 13
So, the expression 16x - 13 is not equivalent to 6x - 13. The correct equivalent form of the given expression is 16x - 13.
7x + 2(2x - 5) - (-5x + 3)
= 7x + 4x - 10 + 5x - 3
= 16x - 13
So, the expression 16x - 13 is not equivalent to 6x - 13. The correct equivalent form of the given expression is 16x - 13.
is this equivalent 11x - 10 + 3 - 5x
Let's simplify the expression 11x - 10 + 3 - 5x:
11x - 10 + 3 - 5x
= (11x - 5x) + (-10 + 3)
= 6x - 7
The expression 11x - 10 + 3 - 5x simplifies to 6x - 7, which is not equivalent to the original expression 7x + 2(2x - 5) - (-5x + 3).
Therefore, the expression 11x - 10 + 3 - 5x is not equivalent to 7x + 2(2x - 5) - (-5x + 3).
11x - 10 + 3 - 5x
= (11x - 5x) + (-10 + 3)
= 6x - 7
The expression 11x - 10 + 3 - 5x simplifies to 6x - 7, which is not equivalent to the original expression 7x + 2(2x - 5) - (-5x + 3).
Therefore, the expression 11x - 10 + 3 - 5x is not equivalent to 7x + 2(2x - 5) - (-5x + 3).
is this equivalent 11x - 10 + 5x - 3
Let's simplify the expression 11x - 10 + 5x - 3:
11x - 10 + 5x - 3
= (11x + 5x) + (-10 - 3)
= 16x - 13
Therefore, the expression 11x - 10 + 5x - 3 is indeed equivalent to the original expression 7x + 2(2x - 5) - (-5x + 3), which simplifies to 16x - 13.
11x - 10 + 5x - 3
= (11x + 5x) + (-10 - 3)
= 16x - 13
Therefore, the expression 11x - 10 + 5x - 3 is indeed equivalent to the original expression 7x + 2(2x - 5) - (-5x + 3), which simplifies to 16x - 13.